Quantitative Determination of Gallic Acid from Methanolic Extract of Cocculushirsutus using HPTLC - Meena, Mukesh kumar (International Journal of Pharmaceutical & Biological Archive, 2017)
Cocculushirsutus is antipyretic, tonic, lessens thirst, good for fractures and useful in tubercular glands related problems. It is a well-known herb used as first aid remedy in minor injuries. During the present study a rapid, simple, accurate and specific HPTLC method for quantitative estimation of Gallic acid present in the dried leaf powder and callus of C. hirsutus has been developed. The method used in this work resulted in good peak shape and enabled good resolution of Gallic acid from C. hirsutussamples. Gallic acid was identified in invivo (leaf) and in vitro (six weeks old callus) tissues. Presence of isolated Gallic acid was further confirmed by super imposable IR spectra of isolated and authentic samples of Gallic acid. Variation in Gallic acid content in in-vivo and in-vitro samples in C. hirsutuswas observed. In vivoleaf had maximum amount of Gallic acid (0.44%) while minimum amount was found in in vitro callus (0.10 %). High content of Gallic acid in leaf shows its potential of synthesizing Gallic acid. This study is also of practical importance because Gallic acid has quite interest of in food, cosmetic and pharmaceutical industries, as substitutes for synthetic antioxidants. The Gallic acid exhibit a wide range of biological effects including antibacterial, anti-inflammatory, antiallergic, hepatoprotective, antithrombotic, antiviral, anticarcinogenic and vasodilatory actions.